2014
DOI: 10.1016/j.eats.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Particulated Juvenile Cartilage Allograft Transplantation for the Treatment of Osteochondral Lesions of the Talus

Abstract: Several options exist for the treatment of osteochondral lesions of the talus. Particulated juvenile cartilage allograft transplantation (PJCAT) has become a viable treatment modality for osteochondral lesions of the talus that are not amenable to microfracture or for which microfracture has failed. Arthroscopic placement of this type of graft obviates the need for osteotomy or plafondplasty and does not prevent additional procedures from being performed through an anterior approach. Special instrumentation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 12 publications
(6 reference statements)
0
23
0
Order By: Relevance
“…This technique has the potential to replace hyaline cartilage architecture without donor site morbidity [ 85 ]. Particulated juvenile cartilage can be performed through either open or arthroscopic techniques without malleolar osteotomy because it does not require perpendicular access to the lesion as is often needed for autograft or allograft transfer [ 86 ]. However, if the lesions are unreachable, malleolar osteotomy can be performed if needed.…”
Section: Surgical Strategiesmentioning
confidence: 99%
“…This technique has the potential to replace hyaline cartilage architecture without donor site morbidity [ 85 ]. Particulated juvenile cartilage can be performed through either open or arthroscopic techniques without malleolar osteotomy because it does not require perpendicular access to the lesion as is often needed for autograft or allograft transfer [ 86 ]. However, if the lesions are unreachable, malleolar osteotomy can be performed if needed.…”
Section: Surgical Strategiesmentioning
confidence: 99%
“…The investigators noted that based on their 6-month follow-up data, this process was visualized as incomplete (1). Adams et al (25) reported their experience with arthroscopically guided juvenile cartilage transplantation and concluded that juvenile particulate cartilage can be successfully used to treat talar lesions using arthroscopic techniques. A critical need exists to objectively assess cartilage repair tissue quality, which could serve as a biomarker for monitoring and predicting surgical and clinical outcomes in longitudinal studies (26).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, specifically for the knee successful results have been reported for the patella, trochlea and condyle with and without concurrent surgeries 5 . Treatment of talar lesions using arthroscopic techniques have also been described with comparable results to open methods 11, 12. Size of the lesion is important for preoperative planning with less reliable results in lesions >3 cm 2, 13…”
Section: Discussionmentioning
confidence: 99%